USE OF GREEN FINE GREEN: A BRIEF REVIEW OF PATENTS - Shegelman I. R., Vasilyev A. S., Kirilina V. M. (Relevant lines of scientific research: theory and practice, 2019)
considered patents aimed at developing new intellectual property in the field of technologies and equipment for the use of green fir wood.
Keywords: патент; база знаний; knowledge base; patent; древесная зелень; недревесные ресурсы леса; wood greens; non-timber forest resources; пихта; fir